Runs of homozygosity implicate autozygosity as a schizophrenia risk factor. - Matthew C Keller; Matthew A Simonson; Stephan Ripke; Ben M Neale; Pablo V Gejman; Daniel P Howrigan; Sang Hong Lee; Todd Lencz; Douglas F Levinson; Patrick F Sullivan; Schizophrenia Psychiatric Genome-Wide Association Study Consortium (PLoS Genetics)
Autozygosity occurs when two chromosomal segments that are identical from a common ancestor are inherited from each parent. This occurs at high rates in the offspring of mates who are closely related (inbreeding), but also occurs at lower levels among the offspring of distantly related mates. Here, we use runs of homozygosity in genome-wide SNP data to estimate the proportion of the autosome that exists in autozygous tracts in 9,388 cases with schizophrenia and 12,456 controls. We estimate that the odds of schizophrenia increase by ~17% for every 1% increase in genome-wide autozygosity. This association is not due to one or a few regions, but results from many autozygous segments spread throughout the genome, and is consistent with a role for multiple recessive or partially recessive alleles in the etiology of schizophrenia. Such a bias towards recessivity suggests that alleles that increase the risk of schizophrenia have been selected against over evolutionary time.